Pengaruh Frekuensi POC Rebung terhadap Pertumbuhan dan Produktivitas Tanaman Sawi (Brassica juncea L.) - Maylani Lucky (Hunatech Vol. XXX, No. XXX, 2022)
Mustard (Brassica juncea L.) is one type of horticultural plant that has good prospects for development. The organic fertilizers used can be in the form of liquid organic fertilizers and solid organic fertilizers. Efforts to increase the productivity of mustard plants with organic fertilization have not been satisfactory. The use of liquid organic fertilizer (POC) is considered to be able to quickly overcome nutrient deficiencies and be able to provide nutrients quickly for mustard plants. The purpose of this study was to determine the effect of POC of bamboo shoots extract on the growth and yield of mustard plants, and to determine the frequency of POC of bamboo shoots extract on the growth and yield of mustard plants. This study used a completely randomized design (CRD) with one factor, namely the frequency of organic fertilizers (f) with 5 levels of treatment and each treatment consisted of 4 replications and each treatment unit consisted of 4 plants, so that in total there were 80 plants. Treatment frequency of liquid organic fertilizer for bamboo shoots (f) is: f1: frequency of 3 days, f2: frequency of 6 days, f3: frequency of 9 days, f4: frequency of 12 days, f5: frequency of 15 days. Observation variables were plant height (cm), leaf (strand), leaf width (cm) and plant fresh weight (g). The frequency of POC of bamboo shoots has an effect on the growth and yield of mustard plants. The frequency of presenting POC bamboo shoots once every 3 days gave high yields, namely 12.37 cm at plant height 2 WAP, and 13.58 cm at plant height 3 MST, at 2 MST leaf number was 10.13 strands, leaf number 3 MST was 12,31 strands, plant fresh weight was 25.81 g/plant and leaf area was 7.11 cm. presenting POC bamboo shoots once every 6 days was considered more effective because it gave the same results as the treatment that gave the highest yield on the variable.